Elements for a business model in specialized services. The case of the international roaming - Acevedo Borrego, Adolfo (2008)
Roaming is a service of mobile communications where the clients of a switch named home network, can use cellular service in another different network named visited network. It is the capacity of a mobile user to carry out and to receive calls with same cellular number when he travels another countries. This article presents the elements for the service infrastructure development, considering that represents an opportunity of business.